2019
DOI: 10.1016/j.euf.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomic Analysis of Coincident Cancer Foci Implicates CTNNB1 and PTEN Alterations in Ductal Prostate Cancer

Abstract: The aggressive subtype ductal adenocarcinoma is closely related to conventional acinar prostate cancer. Ductal foci contain additional alterations, however, leading to frequent activation of two targetable pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 44 publications
2
43
1
Order By: Relevance
“…Although we did not intentionally sequence the acinar carcinoma component in patients with mixed ductal-acinar tumors, the fact that concurrent ductal and acinar carcinomas share common ERG rearrangements and other alterations suggests that the DDR alterations are likely shared between these components as well. 4,9 This study adds to the literature suggesting that aggressive histologic subtypes of localized prostate cancer (eg, primary Gleason pattern 5 acinar carcinomas, small cell carcinomas, and now dPCs) may be enriched for MMR defects. 25…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Although we did not intentionally sequence the acinar carcinoma component in patients with mixed ductal-acinar tumors, the fact that concurrent ductal and acinar carcinomas share common ERG rearrangements and other alterations suggests that the DDR alterations are likely shared between these components as well. 4,9 This study adds to the literature suggesting that aggressive histologic subtypes of localized prostate cancer (eg, primary Gleason pattern 5 acinar carcinomas, small cell carcinomas, and now dPCs) may be enriched for MMR defects. 25…”
Section: Discussionmentioning
confidence: 73%
“…Similar to a prior report, we found that PTEN alterations were generally mutually exclusive of mutations in genes associated with WNT-signaling activation (eg, APC and CTNNB1 mutations), although there was one patient with a pathogenic MSH2 mutation that had secondary alterations in APC , PTEN , and PIK3R1 . 9 There were three additional patients in whom WNT-pathway alterations co-occurred with PI3K-pathway alterations, including one patient with an APC and PIK3CA mutation, and two patients with CTNNB1 and PIK3CA mutations. Compared with patients with CRPC, there were fewer PTEN alterations and more PIK3CA mutations in our dPC cohort, with an overall similar incidence of PI3K-pathway alterations (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The oncogenic ß-catenin activation cooperates with Pten loss to decrease the latency of prostate cancer progression. Almost half of the prostate cancer cases with the CTNNB1 mutation have associated PTEN haploinsufficiency (34). Interestingly, ß-catenin-mutant prostate tumors with Pten haploinsufficiency exhibit further loss of Pten, mimicking Pten-null ß-catenin-mutant tumors.…”
Section: Discussionmentioning
confidence: 99%